Bill & Ted's excellent adventure [videorecording (Blu-Ray)] - Reeves, Keanu; Carlin, George; Winter, Alex, 1965-; Shor, Dan; Matheson, Chris; Solomon, Ed; Kroopf, Scott; Murphey, Michael S.; Soisson, Joel; Herek, Stephen (Metro Goldwyn Mayer Home Entertainment, 2012)
Bill and Ted spent so much time forming their rock band, that they're flunking history. A guardian angel from the future, Rufus comes to them with a time traveling phone booth to take them in to the past to learn from history's most influential people. The journey turns out to be a blast, but will they learn enough to pass their class.